The effects of entrepreneurial orientation and environmental uncertainty on Korean technology firms' R&D investment - Jaewook Yoo; Junic Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
This study aims to examine the relationship between top managers' entrepreneurial orientation and firms' research and development (R&D) investment and the moderating effects of environmental uncertainty on this relationship. Using a sample of 337 Korean technology firms, we implemented a multiple regression analysis with R&D intensity as a dependent variable, top managers' entrepreneurial orientation as an independent variable, and environmental uncertainty as a moderating variable. The findings reveal that the entrepreneurial orientation of top managers has significant and positive relationships with firms' strategic decisions regarding R&D investment. This implies that the tendencies and characteristics of top managers significantly influence firms' innovation efforts, especially during an economic recession. Furthermore, environmental munificence intensifies the entrepreneurial orientation and R&D investment relationship, while environmental dynamism has a negative moderating effect. On the other hand, environmental hostility does not have any impact on this relationship. The moderating effects of environmental uncertainty imply that firms should carefully consider environmental dynamism and munificence to intensify the positive effect of top managers' entrepreneurial orientation on firms' innovation efforts.
Keywords: 650; entrepreneurial orientation; R&D intensity; innovation; economic recession; environmental uncertainty; open innovation